Morphological, Optical and Wettability Characterization of Honeycomb Patterned Films Based on Self-Assembling Copolymer Under Thermal Annealing - Sanchez-Poblete, J (Elsevier B.V., 2020)
A series of honeycomb-patterned porous films based on self-assembly block copolymers with different hydrophilic blocks were prepared using the breath figure (BF) method. The variation of hydrophilic moieties into the block copolymers provokes a response in the pore diameter size dispersity and in the surface pore distribution entropy. The morphological properties are examined using SEM and AFM microscopies, wettability properties were also studied. The distribution of the pores at the surface and shape variations of the structured films were studied by Raman spectroscopy before and after thermal annealing. We report a significant increase of the order and dispersity narrowing of the pores after thermal annealing which affects the water contact angle (WCA). These results were attributed to the process mechanism of the polymer chain self-assembly of the different hydrophilic moieties as a result of thermal annealing at temperatures below the glass transition temperature (Tg). © 2020 Elsevier B.V.